Effect of Comprehensive Income and Consumption Taxes on Human Capital, Economic Growth, and Income Distribution: Endogenous Economic Growth and Empirical Evidence - Lingling Sun; Yasuyuki Nishigaki (Economies)
This research conducts a comparative study of the economic growth and income distribution effects of consumption and comprehensive income taxes by introducing them into an endogenous economic growth model with human capital formation. We obtained the following results. First, consumption tax does not directly suppress economic growth. Instead, it promotes physical capital accumulation, which causes favorable income distribution effects for capital income earners. Second, comprehensive income tax has the direct effects of suppressing economic growth, restraining physical capital accumulation, and increasing labor supply. Third, comprehensive income tax promotes human capital accumulation, which causes a more favorable income distribution for workers. Finally, by conducting an empirical study using international panel data, we show the growth effects of human capital and educational investment and the differentiated growth effects of income and consumption taxes.